Molluscum contagiosum virus infection - Chen, Xiaoying; Anstey, Alex V; Bugert, Joachim J (The Lancet infectious diseases, 2013)
Molluscum contagiosum virus is an important human skin pathogen: it can cause disfigurement and suffering in children, in adults it is less common and often sexually transmitted. Extensive and persistent skin infection with the virus can indicate underlying immunodeficiency. Traditional ablative therapies have not been compared directly with newer immune-modulating and specific antiviral therapies. Advances in research raise the prospect of new approaches to treatment informed by the biology of the virus; in human skin, the infection is localised in the epidermal layers, where it induces a typical, complex hyperproliferative lesion with an abundance of virus particles but a conspicuous absence of immune effectors. Functional studies of the viral genome have revealed effects on cellular pathways involved in the cell cycle, innate immunity, inflammation, and cell death. Extensive lesions caused by molluscum contagiosum can occur in patients with DOCK8 deficiency—a genetic disorder affecting migration of dendritic and specialised T cells in skin. Sudden disappearance of lesions is the consequence of a vigorous immune response in healthy people. Further study of the unique features of infection with molluscum contagiosum virus could give fundamental insight into the nature of skin immunity.